PEDAGOGICAL POSSIBILITIES OF DETERMINING THE TALENT OF PRESCHOOL EDUCATORS ON THE BASIS OF A VARIATIVE APPROACH - Rakhmonova Dilfuza Makhmudovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article analyzes the state of the problem of training future teachers of preschool children in modern scientific and pedagogical research. Due attention is paid to the analysis of the theoretical basis of the study, in particular the most famous, authoritative researchers and young scientists in the field of professional training of future teachers of preschool educational organizations. The concept of “professional training”, the subject and object of professional training are defined. Particular attention is paid to the teacher as a key figure in the pedagogical process, as well as to the characteristics that a teacher must have for successful professional activity. The article reveals a number of approaches for assessing the professional activity of a preschool education specialist; the prerequisites for the successful implementation of the professional functions of a teacher are highlighted.